First Record of Aff. Plesiosuchus sp. (Mesosuchia, Metriorhynchidae) in the Kimmeridgian of Le Havre (Normandy, North-Western France): Biometry, Profile of Locomotion, and Paleobiological Consequences - Hua Stéphane (Life)
This is the first record of the biggest Metriorhynchidae, aff. Plesiosuchus sp. in France. The remains consist of a partial vertebral column consisting of 11 vertebrae and an ischium fragment. A new method is proposed to evaluate the individual’s size, which is estimated at 6.5 m. This method, unlike previous approaches, is based only on vertebrae and yields results that are congruent with those based on cranial remains. The state of preservation has allowed us to test the animal’s ‘profile of locomotion’ to better interpret how it moved. Concerning other metriorhynchids, the record of Dakosaurus in France based only on teeth must be reassessed, and the genus Torvoneustes, if valid, has to be distinguished from Plesiosuchus.